Nodular Fasciitis of the Orbit: A Case Report and Brief Review of the Literature - John E. Riffle; Andrea H. Prosser; Jeffery R. Lee; Julie J. Lynn (Case Reports in Ophthalmological Medicine)
Nodular fasciitis is a benign, reactive, fibroblastic proliferation in which nodules most commonly develop in the subcutaneous or superficial fascia of the extremities. The occurrence of these growths in the orbital region is relatively rare. Our intent is to report another orbital case of this benign fibroproliferative tumor and to provide a brief review of the pertinent medical literature. The salient pathologic features of nodular fasciitis are summarized. The potential for the misdiagnosis of these benign mesenchymal tumors as a malignant sarcomatous neoplasm is discussed. It is important for ophthalmologists to be aware of this pathologic entity and its pseudosarcomatous appearance.